SCN4A p.R675Q Mutation Leading to Normokalemic Periodic Paralysis: A Family Report and Literature Review - Shi, Jiejing; Qu, Qianqian; Liu, Haiyan; Cui, Wenhao; Zhang, Yan; Lv, Haidong; Lu, Zuneng (Frontiers in Neurology, 2019)
To investigate the clinical features, skeletal muscle imaging and muscle pathological characteristics of normokalemic periodic paralysis (NormoKPP) caused by mutation of SCN4A genep.R675Q. Methods The clinical data, skeletal muscle imaging, pathological data, and gene test results of a family with NormoKPP were collected in detail in October 2018. The previous literatures were reviewed and comparative analysis. Results The proband was a 28-year-old male with paroxysmal weakness of both lower limbs for 14 years. Limb weakness was mainly manifested in the proximal extremities of both lower limbs, which occurred 2-3 times a year. The muscle weaknessmyasthenia of each attack lasted for 1-2 weeks and gradually recovered. The blood potassium levels were normal. The abnormal signals of the posterior thigh muscle group and the medial calf muscle group could be seen on the magnetic resonance imaging of skeletal muscle, and the target-fibercentral core could be seen in some muscle fibers in muscle pathology. The father of the proband and his brother had the same symptoms.10 in the family received genetic testing. The results showed that 5 had a mutation of in SCN4A genep.R675Q. The mutation gene came from the father of the proband. Conclusion NormoKPP is a clinically rare form of sodium ion channel disease. The clinical manifestations, skeletal muscle imaging and pathological changes are different from the common hypokalemic periodic paralysis. SCN4A gene detection is an important means for the diagnosis of NormoKPP.